Generation Z Media Literacy Awareness of the Rainbow Symbol on Tik-tok as an LGBT Campaign - Ayu Mujiyanti; Vyki Mazaya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Tik-tok is a social media that has been present in Indonesia since 2018 and was blocked by the Ministry of Communication and Information for one week because it gave negative broadcasts. However, Tik-tok has now spread as a medium for campaigning for various aspects, one of which is the LGBT (lesbian, gay, bisexual and transgender) is a term for people who have deviations in their sexual orientation and are synonymous with the rainbow flag and rainbow symbol. LGBT with rainbow symbol on Tik-tok. The formulation of the problem discussed was regarding how to use the rainbow symbol on Tik-tok as an LGBT campaign and how media literacy awareness of Generation Z on LGBT campaigns in using the rainbow symbol on Tik-tok (Studies on Islamic Communication and Broadcasting Students of UIN KH. Abdurrahman Wahid Pekalongan. The type of research used is qualitative, with data collection techniques of observation, interviews, and documentation. Data analysis used by researchers is using the method from Miles and Huberman, which includes the process of data reduction, data presentation, and drawing conclusions. The results of research on rainbow symbols in some content on Tik-tok are a campaign for LGBT actors in the world, including Indonesia. Although there are two possible uses of the rainbow symbol as something related to aesthetic elements. The results of the analysis of Z generation's media literacy awareness of LGBT campaigns in using the rainbow symbol on Tik-tok (Study on Islamic Communication and Broadcasting Students of UIN K.H. Abdurrahman Wahid Pekalongan) are still not met, namely there are four New Media Literacy frameworks, namely the consumption function includes consuming skills and understanding, critical consumption includes analysis, synthesis, and evaluation, participation functions include prosuming skills and distribution, as well as critical participation.